Pengembangan Sistem Pendukung Keputusan Menentukan Siswa Terbaik dalam Pembelajaran Musikalisasi Puisi pada Kelas XI - Sheila Try Thania; Nila Safina; Rika Kartika; Ali Ali; Rita Rita (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
The need for a more objective and systematic assessment process in poetry musicalization learning encouraged the development of a decision support system to assist teachers in determining the best-performing students. This study aimed to develop an assessment system and evaluate the feasibility and effectiveness of a Decision Support System (DSS) for selecting outstanding students in poetry musicalization learning for Grade XI students. The research population consisted of 23 teachers at MAS Islamic Centre, while the sample included four Indonesian language teachers. This study employed a Research and Development (R&D) approach using the ADDIE development model. The developed system incorporates four assessment criteria: pitch, rhythm, pronunciation, and harmony, which are used to support the decision-making process. The evaluation covered usability, reliability, and integrity aspects, resulting in an average score of 89%, categorized as “Highly Effective,” indicating that the system is operable and suitable for users. Material Expert I assessed the system at 90% (Highly Feasible), while Material Expert II assigned a score of 78% (Feasible). Media Expert I provided a score of 86% (Highly Feasible), and Media Expert II assigned 90% (Highly Feasible). These findings indicate that the developed system is feasible and effective as a technology-based assessment tool to support decision-making in poetry musicalization learning.